Pemanfaatan Google Sebagai Media Literasi Digital Untuk Menjaga Kesehatan Mental Mahasiswa - Ramadhan, Mohamad Riza Rashin; Riswandi, Ervan Arya; Rachman, Ichsan Fauzi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2025)
The rapid advancement of digital technology has transformed how university students’ access and manage information, including mental health resources now readily available through Google. This study aims to examine the role of Google as a digital literacy platform in supporting students' mental health, specifically focusing on their ability to independently search for, verify, and manage mental health information. Using a quantitative survey method, the research involved students from various faculties selected through purposive sampling. The research instrument was a questionnaire based on the Tular Nalar (2020) digital literacy competency indicators, which consist of three levels: Basic, Responsive, and Resilient. The findings reveal that most students actively utilize Google and have a solid basic understanding of its features for searching for mental health information. However, there are gaps in advanced skills, particularly in information verification, content management, and ethical information sharing. These results highlight the need to strengthen digital literacy, emphasizing not only technical skills but also critical and ethical considerations. This study introduces an innovative approach by integrating Google usage with locally relevant digital literacy competency measurements and provides strategic recommendations for developing adaptive digital literacy curricula to address mental health challenges in the digital era.